Analisis Kinerja KSPPS BKK Bersama Kami Kasembadan Dengan Menggunakan pendekatan Balance Scorecard - Cery, Cery; Pransiska, Ega; Oktavianingsih, Wiji; Shafrani, Yoiz Shofwa (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to evaluate the performance of KSPPS BKK Bersama Kami Kasembadan through the application of the Balanced Scorecard (BSC) framework, which comprises four fundamental perspectives: financial, customer, internal processes, and learning and growth. Employing a descriptive quantitative methodology, the data utilized in this research were obtained from the cooperative’s financial statements and internal records spanning the years 2021 to 2024. The results indicate that the cooperative was able to maintain its financial ratios in alignment with the benchmarks established by Bank Indonesia. Moreover, the adoption of door-to-door service strategies and the continuous implementation of employee training programs contributed to enhanced service quality and organizational capability. In conclusion, the use of the BSC served as an effective strategic tool in evaluating and reinforcing the cooperative’s performance in accordance with sharia principles.